Orchid Species Diversity across a Forest Disturbance Gradient in West Mau Forest, Kenya - Mirioba, Job N.; Emitaro, William; Obwanga, Benson; Gaya, Humphrey; Leley, Nereoh; Otuoma, John; Maina, John M.; Kawaka, Fanuel (PLOS One, 2024)
Orchidaceae is one of the most diverse and widespread groups of flowering plants. Despite their immense ecological and socio-economic value, their spatial distribution across forest disturbance gradient is not well understood, particularly in tropical montane forests. This study assessed the influence of forest degradation on orchid species richness and abundance in West Mau Forest, Kenya. Stratified systematic sampling was adopted across three different disturbance regimes consisting of relatively intact forest, moderately disturbed forest and highly degraded forest. A total of five orchid species were recorded from nine hosttree species. The intact forest had seven host tree species with five orchid species. The moderately degraded forest had four host-tree species with two orchid species, while the highly degraded forest that had no orchids. Polystachya confusa was the most abundant orchid species (600.0±227.9 clumps ha-1) followed by Bulbophyllum sp (340.0±112.2 clumps ha-1), Chamaeangis sp (300.0±115.5 clumps ha-1), Aerangis sp (200.0±57.7 clumps ha-1) and Tridactyle sp (100.0±0.0 clumps ha-1). The results of this study indicate that forest degradation reduces orchid species diversity in tropical montane forests. They also show that orchids are bioindicators of forest degradation status.
Keywords: Orchid Species; West Mau Forest